2009
DOI: 10.1186/1471-2431-9-56
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of hospitalization for bronchiolitis in preterm children: a retrospective longitudinal study in Italy

Abstract: Background: Bronchiolitis is a distressing, potentially life-threatening respiratory condition that affects infants. We evaluated the incidence and risk factors of hospitalization for broncholitis in preterm infants (i.e., a gestational age of <36 weeks) born between 2000 and 2006, and the use and impact of Palivizumab, a monoclonal antibody that in randomized clinical trials has been shown to lessen the severity of RSV-related bronchiolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 21 publications
7
29
0
Order By: Relevance
“…The increased risk of respiratory hospital admissions in infants born in the summer months is consistent with known risk factors of hospitalization for bronchioloitis. 27 We also found a protective effect associated with breastfeeding, consistent with other studies. 4,28 Despite high levels of breastfeeding initiation in the United Kingdom (81%), only 22% of mothers continue to breastfeed at 6 months.…”
Section: Discussionsupporting
confidence: 92%
“…The increased risk of respiratory hospital admissions in infants born in the summer months is consistent with known risk factors of hospitalization for bronchioloitis. 27 We also found a protective effect associated with breastfeeding, consistent with other studies. 4,28 Despite high levels of breastfeeding initiation in the United Kingdom (81%), only 22% of mothers continue to breastfeed at 6 months.…”
Section: Discussionsupporting
confidence: 92%
“…Cardiac diagnoses included only if established at 1 of the 3 centres for pediatric cardiology107.0NR1.70 (1.45–1.99)Kristensen 2009 [38]Denmark7-year retrospective, multicenter study (1996–2003) of 3239 children <2 years with heart disease; no child received RSV immunoprophylaxisCategorized as HS-CHD in all patients who were cyanotic, decompensated or required anti-congestive therapy. In other patients hemodynamic significance categorized as determined by the attending pediatric cardiologistCHD/HS-CHD: 102.00–5 months: 71.3 a,b 6–11 months: 73.2 a,b 12–17 months: 43.4 a,b 18–23 months: 29.6 a,b 0–23 months: 56.5 a,b NAHS-CHD: 1.53 (1.04–2.26) c Cardiomyopathy: 5.84 (1.26–27.16) c Medrano López 2010 [5]Spain4-year prospective, multicenter study (2004–2008) of 2613 children <2 years with HS-CHD hospitalized for ARI (3.8% diagnosed RSV); 90.5% received RSV prophylaxisDefinition of HS-CHD stipulated by the Spanish Society of Pediatric CardiologyHS-CHD: 38.0NRNRErikkson 2002 [40]Sweden12-year retrospective study (1987–1998) of 1503 episodes of RSVH in children <2 years; infants with cardiac malformation (2.9% catchment area; 13% from other areas); no data on RSV immunoprophylaxisCardiac malformation/lesion—not definedCHD: 28.0–64.0 d NRNRSimoes 1998 [44]US3-year prospective, multicenter, randomized, controlled study of 416 children <4 years with CHD or cardiomyopathy (214 control group—no RSV immunoprophylaxis)Not definedCHD: 150.0 (control group)<6 months: 240.0 (control group)>6 months: 90.0 (control group)NRNR RSVH rates for studies with mixed populations of infants and children Lanari 2004 [45]Italy6-month retrospective study (1999–2000) of 1214 children <2 years hospitalized for LRTI or developed RSV LRTI whilst hospitalized in 32 tertiary centers (3.5% non-surgically corrected CHD)Not definedCHD: 357.0Nosocomially acquired RSV: 98.0NRNRPezzotti 2009 [43]Italy6-year retrospective cohort study (2000–2006) o...…”
Section: Resultsmentioning
confidence: 99%
“…In a prospective, population-based study of RSVH in premature and term infants by Hall et al [4], infants ≤2 months accounted for an important proportion of all children admitted with RSV infection in the first 2 years of life: 11% were infants <1 month old, 44% were ≤2 months old, and only 36% were >5 months old. In a retrospective longitudinal study of 2407 preterm infants in Italy, the incidence of RSVH declined with age [59]. In this study, significantly higher incidence rates were observed in the first 6 months of life and incidence rates significantly decreased with age ( P  < 0.01), from 89.3/1000 person-years for infants aged 0–6 months to 7.6/1000 person-years for infants aged 12–18 months.…”
Section: Resultsmentioning
confidence: 99%
“…Incidence rates also varied significantly by month of age ( P  < 0.01) and by calendar month ( P  < 0.01). After 18 months of age, however, RSVH was rare [59]. A recent retrospective analysis from the Osservatorio Study in Italy [60], which enrolled three different gestational age group infants (<29, 29 to <32 and 32–35 wGA), found that the percentage of hospitalized preterm infants ≤12 months old that were RSV positive progressively decreased from 40.0% to 28.6% and 18.4% with increasing wGA ( P  = 0.43).…”
Section: Resultsmentioning
confidence: 99%